2021
DOI: 10.1021/acsenvironau.1c00023
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Underestimation of Pesticide Burden for Invertebrates under Field Conditions: Comparing the Influence of Dietary Uptake and Aquatic Exposure Dynamics

Abstract: Pesticides used in agriculture can end up in nearby streams and can have a negative impact on nontarget organisms such as aquatic invertebrates. During registration, bioaccumulation potential is often investigated using laboratory tests only. Recent studies showed that the magnitude of bioaccumulation in the field substantially differs from laboratory conditions. To investigate this discrepancy, we conducted a field bioaccumulation study in a stream known to receive pollutant loadings from agriculture. Our wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 57 publications
1
35
0
Order By: Relevance
“…For each of the two species, one bioconcentration experiment was performed at each of four different temperatures (6, 11, 16 and 21°C). The temperatures represent the range gammarids experience at their collection site (Baumgartner & Robinson, 2015) or in other streams during monitoring studies (Lauper et al, 2021).…”
Section: Bioconcentration Experimentsmentioning
confidence: 99%
See 3 more Smart Citations
“…For each of the two species, one bioconcentration experiment was performed at each of four different temperatures (6, 11, 16 and 21°C). The temperatures represent the range gammarids experience at their collection site (Baumgartner & Robinson, 2015) or in other streams during monitoring studies (Lauper et al, 2021).…”
Section: Bioconcentration Experimentsmentioning
confidence: 99%
“…wastewater treatment plant outflow) were modelled in order to compare the impact of temperature on the internal concentrations of amphipods. For this purpose, the python-based script established and described by Lauper et al (2021) was fed with the Arrhenius' parameters (parent model) determined in the present study. The differential equation (Equation 1) was solved numerically using Heun's method (Ascher & Petzold, 1998).…”
Section: Model Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…These authors reported much lower 24‐h BCFs (between 20 and 70 for exposure at 0.1 µg/L) than the ones determined in the present study, but the authors reported an increasing BCF with increasing exposure time and a maximum value was not established. Underestimation of the bioconcentration potential of neonicotinoids in amphipods is also well established in the literature and may be attributed to binding of the insecticide to biomolecules and the exoskeleton of the organisms (Chen & Kuo, 2018; Lauper et al, 2022; H. Li et al, 2021). In the present study, the lower BCFs of indoxacarb and thiacloprid at the higher treatment level can result from the saturation of uptake mechanisms or changes in the physiological condition of the larvae which reduce uptake, for example reduced respiration rate and immobilization (Mackay & Fraser, 2000).…”
Section: Discussionmentioning
confidence: 92%